Class is not dismissed! - Daneshvari, Gitty (Daneshvari, Gitty. School of fear (New York, N.Y.), 2010)
Thirteen-year-olds Madeleine, Theo, and Lulu, fourteen-year-old Garrison, and ten-year-old new "contestant" Hyacinth, must face their phobias and join forces to learn who is stealing wigs and pageant trophies from the School of Fear.